FINTECH IN UZBEKISTAN: CURRENT STATUS AND DEVELOPMENT PROSPECTS (World Economics and Finance Bulletin, 2026)
The rapid development of the financial technology (fintech) sector in Uzbekistan is associated with state policy, an increase in the volume of digital payments, and the participation of international companies. This article analyzes the main directions of fintech, the regulatory environment, existing problems, and development prospects until 2030.
Keywords: Fintech; Uzbekistan; digital payments; online banking services